2015
DOI: 10.3732/ajb.1500223
|View full text |Cite
|
Sign up to set email alerts
|

Euphorbia plant latex is inhabited by diverse microbial communities

Abstract: Our results suggest that Euphorbia plant latex, a putatively hostile antimicrobial environment, unexpectedly supports diverse bacterial and fungal communities. The ecological roles of these microorganisms and potential interactions with their host plants are unknown and warrant further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 98 publications
0
9
0
1
Order By: Relevance
“…The sample types in which half of the environmental microbial community came from unknown, non-Komodo dragon sources, were concrete, logs, plant materials, and plastic. The unknown microbial sources in the case of the logs/plants may be native plant microbial communities or chloroplasts, which we have often seen at high abundance in other internal projects characterizing plant microbiomes ( 18 ); additionally, it is unknown how much time the Komodo dragons interact with these materials or how often the plastic in the dragon’s enclosure was cleaned by the caretakers, all of which will affect how much Komodo dragon microbial material is detected on these items. Importantly, applying a test of independence on designated microbial sources within SourceTracker revealed that each Komodo dragon microbial community (saliva, skin, and fecal) was distinct from each of the others, with saliva classifying as saliva, skin classifying as skin, and feces classifying as feces.…”
Section: Discussionmentioning
confidence: 99%
“…The sample types in which half of the environmental microbial community came from unknown, non-Komodo dragon sources, were concrete, logs, plant materials, and plastic. The unknown microbial sources in the case of the logs/plants may be native plant microbial communities or chloroplasts, which we have often seen at high abundance in other internal projects characterizing plant microbiomes ( 18 ); additionally, it is unknown how much time the Komodo dragons interact with these materials or how often the plastic in the dragon’s enclosure was cleaned by the caretakers, all of which will affect how much Komodo dragon microbial material is detected on these items. Importantly, applying a test of independence on designated microbial sources within SourceTracker revealed that each Komodo dragon microbial community (saliva, skin, and fecal) was distinct from each of the others, with saliva classifying as saliva, skin classifying as skin, and feces classifying as feces.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in Euphorbia latex, a study measuring communities using culture-independent methods unexpectedly revealed complex bacterial (mean: 44 species per sample; 9 plants analyzed) and fungal (mean: 20.9 species per sample; 22 plants analyzed) communities contained in these latexes [148]. Many of the identified taxa are known plant endophytes but have not been found in latex previously.…”
Section: Endophytic Microorganisms Inhabiting Latex?mentioning
confidence: 99%
“…However, limitations do exist in all NGS platforms employed (Lindahl et al, 2013), and sequence databases for fungi are currently biased toward soil‐dwelling macrofungi (Kõljalg et al, 2013). Despite current technical shortcomings, researchers have used NGS technology to study microbial diversity across a broad range of habitats (Bálint et al, 2015; Gunawardana et al, 2015; Eusemann et al, 2016). Investigations into the microbiota of understudied plant lineages (e.g., seed‐free plants) using NGS technology should also be pursued.…”
mentioning
confidence: 99%